2016
DOI: 10.1111/apm.12564
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of systemic autoimmune rheumatic diseases and clinical significance of ANA profile: data from a tertiary hospital in Shanghai, China

Abstract: It is necessary and useful to explore prevalence of various systemic autoimmune rheumatic diseases (SARDs) in patients with suspicion of having SARDs and to characterize antinuclear antibodies (ANA) profile for identifying different populations (SARDs and non-SARDs). A total of 5024 consecutive patients with available medical records were investigated, whose sera had been tested for ANA profile, including ANA, anti-dsDNA and anti-extractable nuclear antigen (ENA) antibodies, between 31 January 2012 and 26 Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
(35 reference statements)
1
14
0
1
Order By: Relevance
“…The previous study observed that there was an interaction between IL-37 gene and alcohol drinking in ankylosing spondylitis patients in a case-only study 31 . Ankylosing spondylitis is one of the most common chronic inflammatory autoimmune diseases affecting the axial and/or peripheral skeleton with an estimated prevalence of 0.1–0.9% 32 . Chronic inflammation and cytokines play important roles in the pathogenesis of atherosclerosis and CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study observed that there was an interaction between IL-37 gene and alcohol drinking in ankylosing spondylitis patients in a case-only study 31 . Ankylosing spondylitis is one of the most common chronic inflammatory autoimmune diseases affecting the axial and/or peripheral skeleton with an estimated prevalence of 0.1–0.9% 32 . Chronic inflammation and cytokines play important roles in the pathogenesis of atherosclerosis and CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, anti-PCNA antibodies may be a marker for cutaneous variants of SLE. Our study shows a need to (i) widen the panel of diagnostic antinuclear and anti-mitochondrial antigens used in African patients, (ii) further refine the predictive values of the ANA reactivity to different nuclear and mitochondrial antigens in order to differentiate SLE syndromes in African populations, and (iii) consider anti-PCNA reactivity, which has so far been largely excluded in Africa and elsewhere, 43 as a diagnostic marker for patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…In the genesis of cardiac, pulmonary and renal vessels lesions act the activation of pro-inflammatory cytokines and violation of vascular endothelial function It should be noted that in the experimental autoimmune vascular pathology there is a complex system of protection of endothelial cells, which is directed to inhibition of pro-inflammatory cytokines, matrix metalloproteinases and C-dependent protein kinase [17]. Protection of nitrogen oxide relatively to endothelial dysfunction is negligible, and in the linear mice C57Bl/B6j, NZB/W and MRL/1 with immune disorders the additional input of autoantibodies to the basement membrane of vessels is accompanied by the generation of molecules of nitric oxide, but it does not prevent the adhesion of neutrophils to the endothelium of the capillaries and progression of the pathological process [18][19][20]. Bradykinin can suppress the signs of endothelial dysfunction in model of autoimmune systemic disease that enhances vasodilation [21,22].…”
Section: Discussionmentioning
confidence: 99%